2017
DOI: 10.7863/ultra.16.05060
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Contrast-Enhanced Ultrasound Compared With Magnetic Resonance Imaging in Assessing the Tumor Response After Neoadjuvant Chemotherapy for Breast Cancer

Abstract: Contrast enhanced US is a valuable imaging modality for assessing the treatment response in patients receiving NAC and had a comparable correlation as MRI with breast cancer size at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…A recent study also suggested that contrast enhanced US was as effective as MRI (75% accuracy for both) in predicting pCR based on a group of 15 patients. 30 In this study, we found that US and MRI were comparable in predicting pCR in terms of sensitivity, specificity, and NPV, though MRI had slightly higher accuracy and PPV than US. It should be noted that US+MRI had extremely high specificity and PPV, which were comparable with that reported in a recent study that showed MRI combined with second-look US was useful in predicting pCR with specificity and PPV as high as 97.3% and 86.8%.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study also suggested that contrast enhanced US was as effective as MRI (75% accuracy for both) in predicting pCR based on a group of 15 patients. 30 In this study, we found that US and MRI were comparable in predicting pCR in terms of sensitivity, specificity, and NPV, though MRI had slightly higher accuracy and PPV than US. It should be noted that US+MRI had extremely high specificity and PPV, which were comparable with that reported in a recent study that showed MRI combined with second-look US was useful in predicting pCR with specificity and PPV as high as 97.3% and 86.8%.…”
Section: Discussionmentioning
confidence: 51%
“…So US can not accurately measure the volume of the lesion and not accurately observe the spatial distribution of lesional blood flow (13). Breast MRI is the most sensitive examination for breast tumor detection and it can be used to detect the spatial relationship between the lesion and the surrounding tissue, the spatial distribution of lesional blood flow as well (14)(15)(16)(17)(18). What's more, MRI can be used to assess tissue necrosis after ablation by administrating contrast agent (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CEUS to predict a pathological complete response in patients with breast cancer who have received NAC has been reported previously [20][21][22][23][24][25]. In a study of 63 patients, Amioka et al [20] reported that both the peak intensity and the ascending slope were significantly lower in those who achieved a pathological complete response than in those who did not.…”
Section: Discussionmentioning
confidence: 68%
“…The reason for performing the second CEUS examination after the first cycle was that prediction of the response at an early time point is important for treatment modification in non-responders [3,4]. Several studies have evaluated the ability of CEUS to predict early response to NAC [20][21][22][23][24][25]. CEUS is superior to conventional imaging methods when measuring angiogenic changes as an indicator of response.…”
Section: Introductionmentioning
confidence: 99%